Unemployment: skills, gender and social exclusion - BOROOAH, Vani K. (European Spatial Research and Policy, 1998)
The demand for unskilled labour has collapsed across all the countries of the OECD. In the United States, this showed up primarily in falling real wages for less-educated men; in the countries of Europe. it took the form of increased joblessness for the less skilled. Consequently, there was a reduction in both the number of unskilled jobs available and also in the real wages associated with such jobs. In explaining this collapse, US economists emphasise the role of technology, while European economist emphasise the role of trade. In fact the two causes are not independent but highly related. These changes have affected males particularly badly because much of job-creation in OECD countries has been in part-time jobs which have mainly been taken by women. High and stubborn male joblessness has, in tum, led to the creation of an 'underclass' so that a perversion of values and attitudes transforms people from being unemployed to becoming unemployable.